Elementary statics - Triola, Mario F. (London, 2003)
Elementary Statistics has been written for the introductory statistics course and students majoring in any field. Although the use of algebra is minimal, students should have completed at least an elementary algebra course. In many cases, underlying theory is included, but this book does not stress the mathematical rigor more suitable for mathematics majors